MODERN APPROACH TO THE CHOICE OF ANESTHETIC MANAGEMENT DURING COMPUTED TOMOGRAPHY IN CHILDREN WITH CENTRAL NERVOUS PATOLOGY - Роман Васильевич Жданов; Евгений Валерьевич Григорьев; Василий Васильевич Жданов; Евгений Викторович Ивлев; Александр Владимирович Ушаков; Елена Эдуардовна Рубан (Медицина в Кузбассе)
Thus, the analysis of domestic and foreign literature suggests that to date there is no clear choice of anesthetic technique algorithms during computed tomography in children. Although it is possible to use both intravenous anesthetic and inhalation applying last longer limited induction necessity presence anesthetist close to the patient and applying the mask on the face, which may put the computer head during imaging. Do not forget about such a complication inhalation anesthesia as malignant hyperthermia, which occurs more frequently in children than in adults, as well as the absence of dantrolene in the arsenal of the Russian anesthetist, in fact the only means for the treatment of this deadly complication. Any intravenous anesthetic is not without drawbacks, particularly in this group of patients, so the use of routine methods unsafe. Revealing the regularities characteristic of the course of anesthesia during computed tomography for children with CNS pathology will allow objectify approach to the choice of anesthetic. Given the concomitant neurological pathology, different age it makes sense to develop the scale of the forecast of complications in children. Structuring forecast occurrence of complications in this group of children on the selection of anesthetic followed by the construction of prognostic score based on the evidence seems to be promising in terms of reducing the risk of anesthesia.